Colonial progress and countryside conservatism : an essay on the legacy of Van der Lingen of Paarl, 1831-1875 - Du Plessis, Jean (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1988.